Epidemiological characteristics of burns patients treated in the emergency services of Ministry of Health facilities in Peru - Cornejo-Luyo, Viviana L. (2025)
Introduction. Burns are a public health problem because of their consequences and burden on health systems. Objective. We describe the epidemiological characteristics of burns treated in the emergency services of the Ministry of Health (MINSA) facilities in Peru. Methods. We conducted a descriptive observational study with data from patients registered in the database ‘Morbidity in hospital emergency - MINSA’ between January 2021 and April 2022. Results. We identified 10 093 cases of burns. There was a higher frequency in children aged 1 to 4 years with 2805 cases (27.7%). 250 patients were categorized as major burns. Level II-1 and II-2 health centers are the ones that most frequently treat burn patients and there was a higher frequency of second-degree burns (53.2%). Conclusion. Burns generate an important demand in the emergency services of MINSA health facilities.